Bridging Digital Divide Among Demographics: Need, Barriers and Ways - Nupur (Gyan Management Journal, 2024)
With the help of service delivery through mobile phones and other electronic devices using internet, there is a reduction in the fatigue of customers. And this is a positive note in digitalization of public electronic service delivery system. But the spread of information and communication technology and digital transformation across the world has given birth to digital divide especially in developing and developed countries. The unequal distribution of income, age disparity, gender differences and differing educational background are the bases on which the gap is widening. Digital competency is a necessity. For bridging the gap, no one can afford to be left behind. Present study is an attempt to understand the need and challenges faced in eliminating digital divide and the possible ways to handle the problem.